Ischemic Stroke Activates Hematopoietic Bone Marrow Stem Cells. Issue 3 (30th January 2015) - Courties, Gabriel; Herisson, Fanny; Sager, Hendrik B.; Heidt, Timo; Ye, Yuxiang; Wei, Ying; Sun, Yuan; Severe, Nicolas; Dutta, Partha; Scharff, Jennifer; Scadden, David T.; Weissleder, Ralph; et al.
<x xml:space="preserve">Abstract</x> Rationale: The mechanisms leading to an expanded neutrophil and monocyte supply after stroke are incompletely understood. Objective: To test the hypothesis that transient middle cerebral artery occlusion (tMCAO) in mice leads to activation of hematopoietic bone marrow stem cells. Methods and Results: Serial in vivo bioluminescence reporter gene imaging in mice with tMCAO revealed that bone marrow cell cycling peaked 4 days after stroke (P<0.05 versus pre tMCAO). Flow cytometry and cell cycle analysis showed activation of the entire hematopoietic tree, including myeloid progenitors. The cycling fraction of the most upstream hematopoietic stem cells increased from 3.34%±0.19% to 7.32%±0.52% after tMCAO (P<0.05). In vivo microscopy corroborated proliferation of adoptively transferred hematopoietic progenitors in the bone marrow of mice with stroke. The hematopoietic system's myeloid bias was reflected by increased expression of myeloid transcription factors, including PU.1 (P<0.05), and by a decline in lymphocyte precursors. In mice after tMCAO, tyrosine hydroxylase levels in sympathetic fibers and bone marrow noradrenaline levels rose (P<0.05, respectively), associated with a decrease of hematopoietic niche factors that promote stem cell quiescence. In mice with genetic deficiency of the β3 adrenergic receptor, hematopoietic stem cells did not enter the cell cycle in increased numbers after tMCAO (naive control, 3.23±0.22; tMCAO, 3.74±0.33, P=0.51). Conclusions: Ischemic stroke activates hematopoietic stem cells via increased sympathetic tone, leading to a myeloid bias of hematopoiesis and higher bone marrow output of inflammatory Ly6Chigh monocytes and neutrophils.